2005
DOI: 10.3349/ymj.2005.46.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of p16 Protein Expression Loss and Aberrant p53 Protein Expression in Pancreatic Cancer

Abstract: Pancreatic cancer is a disease with poor prognosis mainly due to low resection rates and late diagnosis. To increase resectability and improve survival rates, a better understanding of pancreatic cancer pathogenesis and more effective screening techniques are required. New methods, such as genetic and molecular alterations, may suggest novel approaches for pancreatic cancer diagnosis and treatment. We immunohistochemically investigated 44 formalin-fixed, paraffin-embedded specimens of pancreatic ductal adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
0
27
2
3
Order By: Relevance
“…Methylation was seen in 33% of the whole series and it was, like K-Ras mutation, significantly associated with a M þ phenotype (univariate analysis P ¼ 0.011; multivariate analysis P ¼ 0.001). A strong correlation between staging and p16INK4A methylation was found also by Yi et al (2001); loss of p16INK4A expression has been previously associated with lymph-node metastases (Kim et al, 2005a) and more advanced stage (Jeong et al, 2005). Altogether, these results suggest that p16INK4A methylation might link to a more malignant phenotype in CRC; interestingly Liang et al (1999) recently reported an association between p16INK4A methylation and shorter survival of CRC.…”
Section: Discussionmentioning
confidence: 57%
“…Methylation was seen in 33% of the whole series and it was, like K-Ras mutation, significantly associated with a M þ phenotype (univariate analysis P ¼ 0.011; multivariate analysis P ¼ 0.001). A strong correlation between staging and p16INK4A methylation was found also by Yi et al (2001); loss of p16INK4A expression has been previously associated with lymph-node metastases (Kim et al, 2005a) and more advanced stage (Jeong et al, 2005). Altogether, these results suggest that p16INK4A methylation might link to a more malignant phenotype in CRC; interestingly Liang et al (1999) recently reported an association between p16INK4A methylation and shorter survival of CRC.…”
Section: Discussionmentioning
confidence: 57%
“…The positive rate of PCNA in PDX-1-positive samples was as high as 78.2%, whereas that in PDX-1-negative samples was only 36.4%, suggesting that PDX-1-positive cells had higher potential of proliferation. Many studies have demonstrated high frequency of mutations of oncogene such as K-ras and tumor suppressor genes such as p16, p53 in pancreatic cancer tissues and cell lines [8,18,19] . Based on our study, we deduced that the alteration of PDX-1 expression might represent one of those genetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of p16 Ink4a in premalignant lesions and its loss during malignant transformation have been demonstrated in the carcinogenesis of the liver, lung and pancreas. [7][8][9] Loss of p16 Ink4a is often caused by CDKN2A (p16 Ink4a ) promoter hypermethylation. 10 This mechanism of gene silencing is associated with the CpG island methylator phenotype (CIMP) of colorectal cancer, which implies widespread promoter methylation including CDKN2A.…”
mentioning
confidence: 99%